Code red for humanity or time for broad collective action? Exploring the role of positive and negative messaging in (de)motivating climate action - Martel-Morin, Marjolaine; Lachapelle, Erick (Frontiers in Communication, 2022)
Despite decades of warning from climate scientists, the international community has largely failed at reining in planet-warming greenhouse gas (GHG) emissions. In this context, scientific assessments of climate change – like those periodic reviews provided by the Intergovernmental Panel on Climate Change (IPCC) – are repeatedly faced with the challenge of communicating the rapidly closing window for securing a livable future on Earth. Yet, it remains unclear whether sounding “code red for humanity” fosters climate action or climate paralysis. The ongoing debate among climate change communication scholars about the (in)effectiveness of fear-based messaging sheds light on three intertwined and often overlooked aspects of emotional appeals in communication: the content of the message frame, the emotional arousal it induces, and the values and dispositions of the audiences receiving the message. While previous work has addressed questions related to one or two of these aspects, this study examines the role of positive and negative messaging in (de)motivating climate action, with particular attention to how messages, emotions and audiences interact in the process of communication. Leveraging data drawn from a sample of environmental group supporters in Canada (N=308), we first identify and describe four unique audiences within supporters of Canada’s environmental movement that vary in their levels of engagement and radicalism. We then examine how negative and positive messaging influence emotional arousal and climate action across audience segments. We find that negative messages about climate change (e.g., sounding “code red for humanity”) can be less mobilizing than positive messaging, even when the message is directed toward relatively engaged audiences and followed by the opportunity to take a specific, actionable and effective action. These findings help shed light on the potential limits of fear-based messaging in the context of a global public health pandemic, while further highlighting the importance of communicating in ways that inspire people through hopeful and optimistic messages.